Pathogenicity analysis of variations and prenatal diagnosis in a hereditary coagulation factor XIII deficiency family. Issue 8 (14th September 2018) - Sun, Liwei; Yan, Qijiang; Wang, Yonghua; Luo, Hualei; Du, Peng; Hassan, Reem; Liu, Li; Jiang, Weiying
ABSTRACT: Objectives: Prenatal diagnosis (PND) procedure is urgent to be established for timely management and fatal consequence prevention of factor XIII deficiency (FXIIID), and variations data among Chinese are very scanty. We aimed to find a novel mutation among Chinese and establish a rapid and precise PND procedure with pathogenicity analysis to contribute to the prevention of postpartum hemorrhage in pregnant women and central nervous system bleeding in newborns. Methods: FXIIID was diagnosed by qualitative and quantitative tests of clot solubility test and enzyme-linked immunosorbent assay, respectively. Variations were detected by direct sequencing of F13A and F13B genes in the pedigree and the unborn fetus. Pathogenicity assessment of variations was based on American College of Medical Genetics and Genomics Guidelines. Results: Ten variants in the F13A gene including a novel missense mutation in exon 10, a nonsense mutation in exon 4, a missense mutation in exon 12, 2 missense mutations in exon 14, 3 polymorphisms in intron 10, 2 polymorphisms in intron 14 were detected. Two variants in the F13B gene including a polymorphism in 3'UTR and a synonymous mutation were detected. The compound heterozygous mutations of the nonsense mutation and a novel missense mutation of the F13A gene caused the deficiency in proband, and the fetus which was evaluated to be unaffected by PND was born successfully and the results were verified by follow-up visits. Discussion: We first established the PND procedure with pathogenicity assessment in FXIIID patients. The F13A gene mutations' spectrum of the Chinese Han population was enriched.